1993
DOI: 10.1128/iai.61.12.5219-5224.1993
|View full text |Cite
|
Sign up to set email alerts
|

Expression of monocyte chemoattractant protein 1 (MCP-1) in adult periodontal disease: increased monocyte chemotactic activity in crevicular fluids and induction of MCP-1 expression in gingival tissues

Abstract: The present study shows that monocyte chemotactic activity in crevicular fluids increases with severity of the disease and that a monocyte chemoattractant, monocyte chemoattractant protein 1 (MCP-1), is expressed as the predominant cytokine of gingival tissues and their fibroblasts treated with Porphyromonas (Bacteroides) gingivalis lipopolysaccharide (P-LPS). High monocyte chemotactic activity in the crevicular fluids was neutralized significantly by antiserum specific for the JE/MCP-1 protein. Marked express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 36 publications
3
57
0
1
Order By: Relevance
“…As MCP-1 expression is important to chemotaxis of the monocytes, the detection of GCF MCP-1 levels, especially in AgP, might clarify whether the MCP-1 expression pattern is different from chronic periodontal diseases. In a previous study, Hanazawa et al 20 examined MCP-1 gene expression in gingival tissues and monocyte chemotactic activity in GCF from the patients with periodontal diseases. In the findings of their study, marked MCP-1 gene expression was demonstrated in gingival tissues from chronic periodontal patients but not in those from healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As MCP-1 expression is important to chemotaxis of the monocytes, the detection of GCF MCP-1 levels, especially in AgP, might clarify whether the MCP-1 expression pattern is different from chronic periodontal diseases. In a previous study, Hanazawa et al 20 examined MCP-1 gene expression in gingival tissues and monocyte chemotactic activity in GCF from the patients with periodontal diseases. In the findings of their study, marked MCP-1 gene expression was demonstrated in gingival tissues from chronic periodontal patients but not in those from healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, the immunopathogenic mechanisms in the aggressive form of periodontal diseases have not been completely elucidated. Although the expression of MCP-1 in gingival tissue samples with chronic periodontal disease and chemotactic activity of monocytes in gingival crevicular fluid (GCF) have been investigated in previous studies, 20,21 to our knowledge there is not any report examining and comparing the levels of MCP-1 in GCF samples obtained from patients with chronic periodontitis (CP) and AgP. The investigation of MCP-1 levels in GCF and the relationship between GCF levels of MCP-1 and TNF-a seem very important for further understanding the functional role of MCP-1 and TNF-a in chronic and aggressive periodontal diseases.…”
mentioning
confidence: 99%
“…Monocyte chemoattractant protein-1 (MCP-1), a C-C chemokine, is one of the most potent chemoattractants for monocytes and activation of monocytes by endothelium-derived MCP-1 may be an essential step in the cascade of events that ultimately leads to the emigration of monocytes into inflamed tissue [6]. Fibroblasts, mononuclear phagocytes, and endothelial cells express MCP-1 in inflamed gingiva [7], and MCP-1 increases in the crevicular fluids of adult periodontal patients with severity of the disease [8]. Therefore, MCP-1 production by bacterially stimulated gingival endothelial cells should contribute to periodontal disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…rial pathogenesis depends on the production of endogenous IL-6 by periodontal tissues stimulated by the fimbriae. As we previously demonstrated, the fimbriae contribute to the inflammation and alveolar bone loss of periodontal tissues that occurs in chronic periodontal patients via the multipotential action of endogenous inflammatory cytokines such as IL-1, IL-6, TNF-a, MCP-1, and so on [1][2][3]15]. Therefore, these results suggest to us the possibility that, directly or indirectly, IL-6 plays an important role in the fimbria-mediated pathogenesis in chronic periodontal disease; because IL-6 inhibited the fimbria-stimulated FN expression.…”
Section: Resultsmentioning
confidence: 95%
“…Chronic periodontal disease has been characterized by gingival tissue inflammation, loss of periodontal ligament, and alveolar bone resorption. We previously demonstrated that the gene for monocyte chemoattractant protein 1 (MCP-1) was markedly expressed in gingival tissues of patients with advanced periodontitis and that monocyte chemotactic activity in the GCF of chronic periodontal patients increased with the severity of the disease [15]. MCP-1 expression was observed in the fimbria-or lipopolysaccharide-treated human gingival fibroblasts.…”
Section: Resultsmentioning
confidence: 99%